Synthesis of colorless polyimides with high Tg from asymmetric twisted benzimidazole diamines. (5th February 2022) - Yan, Xiaoying; Dai, Fengna; Ke, Zhao; Yan, Kuangguo; Chen, Chunhai; Qian, Guangtao; Li, Hui
Graphical abstract: Highlights: Poly(benzimidazole imide) films with asymmetric and twisted structures was successfully synthesized. These poly(benzimidazole imide)s achieved more prominent properties than traditional poly(benzimidazole imide)s. The semi-aromatic poly(benzimidazole imide)s were expected to be expanded as heat-resistant colorless materials. The effect of various 2′-substitutions on the properties of these poly(benzimidazole imide)s was discussed. Abstract: To prepare colorless polyimide (CPI) films with high thermal properties, an effective design strategy is incorporating asymmetric and twisted structures in the polymer chain-segments. Based on this strategy, 6, 4′-diamino-2′-methyl-1-methyl-2-phenylbenzimidazole (5a) and 6, 4′-diamino-2′-trifluoromethyl-1-methyl-2-phenylbenzimidazole (5b) were synthesized, and two series of their polyimides (semi- and fully aromatic series) were prepared, respectively. The obtained poly(benzimidazole imide)s (PBIIs) with loosely packed but rigid backbones possessed not only high glass transition temperature (Tg ) but also improved optical transparency. In particular, the semi-aromatic system achieved an excellent transmittance about 80% at 400 nm and an outstanding Tg exceeding 400 °C. Furthermore, the influence of various 2′-substitutions on the combination properties of these poly(benzimidazole imide)s was systematically analyzed. These data expand the poly(benzimidazole imide)s as optical materials and provide a feasible method to prepare heat-resistant colorless polymers.